Experimental determination and application of a numerical model of density and viscosity of diesel, biodiesel and vegetable oil blends (Research, Society and Development, 2022)
The current concern about the environment due to emissions of pollutants from the burning of fossil fuels, the main source of energy for internal combustion engines is one of the main problems to be faced by humanity. As such, biomass provides an alternative and sustainable solution to the problem due to the possibility of producing biofuels from renewable energy sources through thermochemical conversions, such as ethanol, biodiesel and vegetable oils. The use of biodiesel and vegetable oils in diesel cycle internal combustion engines can reduce greenhouse gas emissions without changing the physico-chemical properties of the fuel and without damaging the consumption and efficiency of the engine. In order to prove this, we study the influence of physicochemical properties of different proportions of commercial diesel, biodiesel and Jatropha oil, as well as the effectiveness of numerical methods to obtain physicochemical properties, such as density. It was studied in this college project the behavior of the physicochemical properties of viscosity and specific mass in different concentrations of diesel in mixture with biodiesel (B10 - current commercial diesel, B20, B40, B60 and B100) and diesel in mixture with pinion oil in proportions of 2 , 5, 10 and 20% oil in a diesel blend. The results are promising and prove the effectiveness of the applied numerical model in comparison to the experimental results obtained, besides obtaining results on the flow of each fuel mixture in internal combustion engines.